Phenotypic Characterization and Gene Mapping of a Spiral Leaf and Dwarf (sld) Mutant from Tetraploid Common Tobacco (Nicotiana tabacum L.) - Wang, Shaomei; Wu, Xinru; Guo, Yongfeng; Wang, Dawei; Cheng, Lirui; Wang, Yuanying; Yang, Aiguo; Liu, Guanshan (Agronomy (Basel), 2023)
Leaf morphology and plant height are two agronomic traits closely related to tobacco (Nicotiana tabacum L.) yield and quality. The study of leaf morphology and plant stature mutants will greatly contribute to the fields of plant architecture breeding and developmental biology. Here, we report the characterization of a spiral leaf and dwarf (sld) mutant identified from an ethylmethane sulfonate (EMS)-induced common tobacco population. The sld mutant displayed the phenotype of wrinkled, spiral, and miniature leaves, with the growth point as the central axis and plant dwarfing with shortened internodes. The inheritance pattern of the sld mutant phenotype was manipulated by a recessive nuclear monogene, which was linked to six tobacco simple sequence repeat (SSR) markers from linkage group 5 via gene mapping. Utilizing an F2 population, the sld mutant gene the sld mutant gene was located between the co-segregated markers PT51778, PT54913, and the marker PT61414, with an equal genetic distance of 0.16 cM. Taking advantage of a BC1F1 population, the markers PT51778, PT54913, the sld gene, and the marker PT61414 demonstrated co-segregation, located between the markers PT40040 and PT60933, respectively, with a genetic distance of 1.37 cM and 6.32 cM, respectively. These findings will be helpful in cloning the sld gene and in the further characterization of the regulatory genes controlling the spiral and dwarfing phenotypes in tobacco.